Pain Management for Nerve Injury following Dental Implant Surgery at Tokyo Dental College Hospital. (30th July 2012) - Fukuda, Ken-ichi; Ichinohe, Tatsuya; Kaneko, Yuzuru
Abstract : By allowing reconstruction of compromised occlusion, dental implants contribute to an improvement in quality of life (QOL) and diet. Injury to a nerve during such treatment, however, can result in a sudden decline in QOL. And once a nerve has been injured, the chances of a full recovery are slim unless the damage is only slight. If such damage causes neuropathic pain severe enough to prevent sleep, the patient's QOL will deteriorate dramatically. While damage to skin tissue or bone invariably heals over time, damage to nerves does not, indicating the need to avoid such injury while performing implant insertion, for example. This means not relying solely on X-ray images, which can be rather unclear, but also using computed tomography to allow preoperative planning and intraoperative execution to be performed as accurately as possible. Moreover, if sensory damage does occur it is essential to avoid breaking the bond of trust between dentist and patient by giving false assurances of recovery. In such cases, appropriate measures must be taken promptly. This paper describes pain management for nerve injury following dental implant surgery at the Orofacial Pain Center of Tokyo Dental College Suidoubashi Hospital.